Deliberate Self-Harm and the Elderly: A Volatile Combination—An Overview from the Plastic Surgery Perspective. (19th June 2012) - Packer, J.; Hussain, M. A.; Shah, S. H. A.; Srinivasan, J. R.
Abstract : Aims . To study the factors associated with the DSH in the elderly group of 60 years and above and to recommend changes to be implemented in order to improve the management in this specific group. Materials and Methods . Five-year retrospective study was undertaken from July 2005 to July 2010 in the Plastic Surgery Department of the Royal Preston Hospital, NHS Trust. A Performa was designed to collect data about the inpatient admission and included certain areas of key information. The case notes for all patients were extensively analysed in order to gather adequate information for the devised Performa. Results . DSH is getting more common in the elderly group, and males are more affected than females. 60% of the patients had a previous history of DSH. A large number (80%) of patients had a previous history of mental illness. 60% of those DSH patients were living with family. Almost all patients (90%) were reviewed by the Psychiatry Liaison Team. The timing of patients being assessed was highly variable. Conclusions . Marriage is not a protective factor in the prevention of the DSH in the elderly group. A mental health team referral in the early phases of the management would be of huge benefit and a likely step to prevent possible future admissions. The Department would benefit from the creation of a protocol for the management of these patients. There should be a joint effort of the professionals in the management of DSH in the elderly, and GPs play a very important role in the prevention of DSH in the later life.